A cascade indazolone-directed Ir(iii)- and Rh(iii)-catalyzed C(sp2)–H functionalization/[4 + 2] annulation of 1-arylindazolones with sulfoxonium ylides to access chemically divergent 8H-indazolo [1, 2-a]cinnolines. Issue 19 (19th August 2022) - Zheng, Yi-Chuan; Shu, Bing; Zeng, Yao-Fu; Chen, Shao-Yong; Song, Jia-Lin; Liu, Yan-Zhi; Xiao, Lin; Liu, Xu-Ge; Zhang, Xuanxuan; Zhang, Shang-Shi
Abstract : An indazolone-directed chemoselective synthesis of 8 H -indazolo [1, 2- a ]cinnolines has been realized via a cascade Cp*Ir(iii )- and Cp*Rh(iii )-catalyzed C–H activation/cyclization reaction of 1-arylindazolones with sulfoxonium ylides. Abstract : An indazolone-directed chemoselective synthesis of 8 H -indazolo [1, 2- a ]cinnolines has been realized via a cascade Cp*Ir(iii )- and Cp*Rh(iii )-catalyzed C–H activation/cyclization reaction of 1-arylindazolones with sulfoxonium ylides. The strategy showcased broad substrate scope, high functional group compatibility, mild reaction conditions and was suitable for late-stage modification of drug molecules. Moreover, a preliminary mechanistic probe has been conducted and an exploratory reaction mechanism was proposed. This report represents the first example of an indazolone-directed Cp*Ir(iii )-catalyzed C(sp 2 )–H activation reaction under solvent-free conditions, as well as the first protocol of a Cp*Rh(iii )-catalyzed C(sp 2 )–H activation/oxidation/annulation reaction.